Current status, advancements and development needs of geospatial decision support tools for marine spatial planning in European seas. (1st August 2021) - Depellegrin, Daniel; Hansen, Henning Sten; Schrøder, Lise; Bergström, Lena; Romagnoni, Giovanni; Steenbeek, Jeroen; Gonçalves, Magali; Carneiro, Gonçalo; Hammar, Linus; Pålsson, Jonas; Crona, Jan Schmidtbauer; Hume, Duncan; et al.
Abstract: The implementation of marine spatial plans as required by the Directive on Maritime Spatial Planning (MSP) of the European Union (EU) poses novel demands for the development of decision support tools (DST). One fundamental aspect is the need for tools to guide decisions about the allocation of human activities at sea in ways that are ecosystem-based and lead to sustainable use of resources. The MSP Directive was the main driver behind the development of spatial and non-spatial DSTs for the analysis of marine and coastal areas across European seas. In this research we develop an analytical framework designed by DST software developers and managers for the analysis of six DSTs supporting MSP in the Baltic Sea, the North Sea, and the Mediterranean Sea. The framework compares the main conceptual, technical and practical aspects, by which these DSTs contribute to advancing the MSP knowledge base and identified future needs for the development of the tools. Results show that all of the studied DSTs include elements to support ecosystem-based management at different geographical scales (from national to macro-regional), relying on cumulative effects assessment and functionalities to facilitate communication at the science-policy interface. Based on our synthesis we propose a set of recommendations for knowledge exchange in relation to further DST developments, mechanisms for sharing experience among the user-developer community, and actions to increase the effectiveness of the DSTs in MSP processes. Graphical abstract: Image 1 Highlights: Six decision-support instruments for MSP were analysed. An analytical framework for analysing Decision Support Tools for MSP was developed. Decision Support Tools are multi-objective by nature. Cumulative effects assessment is the most recurrent tool. Operational recommendations for further improvement of Decision Support Tools are provided.